FEATURES OF THE TRAINING OF FUTURE SPECIALISTS IN ELECTRICAL ENGINEERING IN THE CONDITIONS OF THE GREEN TRANSITION - ШВЕДЧИКОВА, І. О.; ПАНАСЮК, І. В.; ДЕМІШОНКОВА, С. А.; СТАЦЕНКО, Д. В. (Technologies and Engineering, 2024)
Purpose. Analysis of the impact of technological changes occurring in the conditions of the green energy transition on the educational programs of training specialists in electrical engineering at the Kyiv National University of Technologies and Design. Methodology. Analysis of the main trends in the development of energy and electromechanics in modern conditions. Analysis of the features of the educational programs of the speciality 141 "Electrical power engineering, electrical engineering and electromechanics" and the content of educational components by education levels in the context of the green energy transition. Findings. Packages of disciplines of the student’s free choice have been developed for all levels of higher education in the speciality 141 "Electrical power engineering, electrical engineering and electromechanics" with an emphasis on acquiring theoretical and practical skills necessary for future work in the profession in conditions of rapid changes. The goals of educational programs have been improved, taking into account the trends of the green transition. Methodological recommendations for the performance of practical (laboratory) work with an emphasis on the study of energy systems based on renewable energy sources and energy storage systems have been developed. An example of the structure of a practical work devoted to the use of an uncontrolled rectifier for a wind generator is provided. Originality. Based on simulation modeling, a complex of research-oriented practical works has been developed, which cover the consideration of a complex of issues, starting from the generation of electricity by renewable energy sources (photoelectric batteries and wind generators) to consumption. Practical value. Practical works developed within the disciplines of free choice and mandatory educational components are intended for use during laboratory and/or practical classes with students of higher education. The knowledge and skills acquired during such classes will become the basis for the formation of green thinking among the students, necessary for the post-war development of the country’s energy sector.